PERBANDINGAN PEMBELAJARAN BERBASIS TEKNOLOGI DAN TANPA TEKNOLOGI PADA PELAJARAN AKHLAK DI MTs MIFTAHUL HUDA - Zahra Aida Kamila; Zahro Nur Annisa; Dila Hilaliah; Aprainto Ependi; Dina Nur Padila; Khalid Ramdhani (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to compare the effectiveness of technology-based learning and conventional learning without technology in the subject of Morals at MTs Miftahul Huda. The method used is a mixed method with a quantitative and qualitative approach. The subjects of the study were grade VIII students who were divided into two groups, namely the control class (conventional learning) and the experimental class (technology-based learning). Data were obtained through pretest and posttest as well as observations during the learning process. The results showed that the average increase in learning outcomes (N-Gain) of students in the control class was 0.66 (66%), while the experimental class only reached 0.59 (59%). This indicates that in this context, conventional methods are more effective in improving moral learning outcomes than the use of technology. The willingness of students and teachers to adopt technology is an important factor in the success of technology-based learning.